The Effectiveness of Herringbone and Buzz Group Techniques to Teach Reading Comprehension for Students with High and Low Reading Habits - Fitriyani, Nunung; Suwandi, Suwandi; Sutopo, Djoko (Universitas Negeri Semarang, 2020)
This research which is based on the condition that the students often find difficulties in comprehending English text aims to investigate the effectiveness of Herringbone and Buzz Group techniques in teaching reading comprehension to students with high and low reading habits. An experimental research with 2x2 factorial designs was applied in this study. The samples of this research were the students of X Busana 1 and X Boga 1 of SMK Assa’idiyah 2 Kudus. Observation, questionnaires, and tests were the instruments of the research. In analyzing the data were used T-test and ANOVA. The results revealed that there was significant difference of the students’ participation on the post-test result after being taught by using Herringbone and Buzz group techniques. Then, the result of the significance value (p value) of teaching technique and student reading habit was 0.00 < 0.05. Thus, it can be stated that there is effective interaction among strategies and participation to enhance students’ reading comprehension.